Enhancing the Antiviral Potency of Nucleobases for Potential Broad-Spectrum Antiviral Therapies - Ruben Soto-Acosta; Tiffany C. Edwards; Christine D. Dreis; Venkatramana D. Krishna; Maxim C-J. Cheeran; Li Qiu; Jiashu Xie; Laurent F. Bonnac; Robert J. Geraghty (Viruses, 2021)
Broad-spectrum antiviral therapies hold promise as a first-line defense against emerging viruses by blunting illness severity and spread until vaccines and virus-specific antivirals are developed. The nucleobase favipiravir, often discussed as a broad-spectrum inhibitor, was not effective in recent clinical trials involving patients infected with Ebola virus or SARS-CoV-2. A drawback of favipiravir use is its rapid clearance before conversion to its active nucleoside-5′-triphosphate form. In this work, we report a synergistic reduction of flavivirus (dengue, Zika), orthomyxovirus (influenza A), and coronavirus (HCoV-OC43 and SARS-CoV-2) replication when the nucleobases favipiravir or T-1105 were combined with the antimetabolite 6-methylmercaptopurine riboside (6MMPr). The 6MMPr/T-1105 combination increased the C-U and G-A mutation frequency compared to treatment with T-1105 or 6MMPr alone. A further analysis revealed that the 6MMPr/T-1105 co-treatment reduced cellular purine nucleotide triphosphate synthesis and increased conversion of the antiviral nucleobase to its nucleoside-5′-monophosphate, -diphosphate, and -triphosphate forms. The 6MMPr co-treatment specifically increased production of the active antiviral form of the nucleobases (but not corresponding nucleosides) while also reducing levels of competing cellular NTPs to produce the synergistic effect. This in-depth work establishes a foundation for development of small molecules as possible co-treatments with nucleobases like favipiravir in response to emerging RNA virus infections.